Enhanced Enzyme-assisted Aqueous Extraction of Polyphenols from Ficus auriculata Fruits: Optimization and Assessment of Bioactive Properties - Pham Thi My Tien; Tran Chi Hai; Nguyen Thi Thanh Lam; Nguyen Minh Tam; Nguyen Ngoc Yen Nhi; Pham Thi Phuong Linh; Le Ngoc Nhu; Phan Van Man (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
The Ficus auriculata fruit is not only a nutritionally valuable food but also a rich source of polyphenols, which contribute to cardiovascular health, cancer prevention, blood sugar regulation, and cholesterol reduction. This study aimed to optimize the extraction conditions for polyphenol-rich extracts from fig fruit using response surface methodology (RSM). The effects of enzyme concentration, solvent-to-solid ratio, and extraction time on total polyphenol content (TPC) were evaluated. The optimized conditions were determined to be an enzyme concentration of 0.74%, a solvent-to-solid ratio of 23:1 (mL/g), and an extraction time of 65 min. Under these conditions, the TPC in the extract reached 2.65 g GAE/100 g dry matter, closely aligning with the predicted value of 2.70 g GAE/100 g dry matter. Scanning electron microscopy (SEM) analysis confirmed significant structural modifications in enzyme-treated samples, indicating enhanced extraction efficiency. Furthermore, GC-MS profiling identified 13 bioactive compounds in the optimized extract, suggesting their potential role in antioxidant activity. These findings highlight the potential of F. auriculata fruit as a valuable source of natural polyphenols, supporting its application in functional foods and pharmaceutical formulations.